Re-engaging with the past: recapitulation of encoding operations during retrieval - Morcom, Alexa (Frontiers in Human Neuroscience, 2014)
Recollection of events is accompanied by selective reactivation of cortical regions which responded to specific sensory and cognitive dimensions of the original events. This reactivation is thought to reflect the reinstatement of stored memory representations and therefore to reflect memory content, but it may also reveal processes which support both encoding and retrieval. The present study used event-related functional magnetic resonance imaging to investigate whether regions selectively engaged in encoding face and scene context with studied words are also re-engaged when the context is later retrieved. As predicted, encoding face and scene context with visually presented words elicited activity in distinct, context-selective regions. Retrieval of face and scene context also re-engaged some of the regions which had shown successful encoding effects. However, this recapitulation of encoding activity did not show the same context selectivity observed at encoding. Successful retrieval of both face and scene context re-engaged regions which had been associated with encoding of the other type of context, as well as those associated with encoding the same type of context. This recapitulation may reflect retrieval attempts which are not context-selective, but use shared retrieval cues to re-engage encoding operations in service of recollection.